The influence of customer incivility towards deviant behaviour: a case study of casual restaurant frontline employees in the Klang valley, Malaysia / Tasnimul Islam and Fahmi Sarin - Islam, Tasnimul; Sarin, Fahmi (Universiti Teknologi MARA, Kedah, 2022)
Over the past decade, the combination of organisational, sociocultural, and technological factors has changed the nature of the work, contributing significantly in developing the service sector. As a large number of people are employed in service occupations, incivility that is being received from customers or clients has become increasingly prevalent in our workplace, especially towards frontline employees. Frontline employees are typically required to tolerate the complaints and frustrations of customers along with other possible stressors often allied with service jobs. Customer rudeness and incivility are believed to be some of the current problems that are widely spreading which trigger frontline employees' deviant attitude. Therefore, the purpose of this study was to investigate the influence of customer incivility over frontline employees' deviant behaviour in casual dining restaurants.